Development of anthropometric characteristics in professional Rugby League players: Is there too much emphasis on the pre-season period?. Issue 8 (13th September 2020) - Morehen, James C.; Clarke, Jon; Batsford, Jake; Highton, Jamie; Erskine, Robert M.; Morton, James P.; Close, Graeme L.
Abstract: Rugby League is a team sport requiring players to experience large impact collisions, thus requiring high amounts of muscle mass. Many players (academy and senior) strive to increase muscle mass during the pre-season, however, quantification of changes during this period have not been thoroughly investigated. We therefore assessed changes in body-composition using Dual X-Ray Absorptiometry (DXA) in eleven academy players over three successive pre-seasons and ninety-three senior players from four different European Super League clubs prior to, and at the end of, a pre-season training period. There was no meaningful change in lean mass of the academy players during any of the pre-season periods (year 1 = 72.3 ± 7.1–73.2 ± 7.2kg; ES 0.05, year 2 = 74.4 ± 6.9–75.5 ± 6.9kg; ES 0.07, year 3 = 75.9 ± 6.7–76.8 ± 6.6kg; ES 0.06) with small changes only occurring over the three-year study period (72.3–75.9kg; ES = 0.22). Senior players showed trivial changes in all characteristics during the pre-season period (total mass = 95.1–95.0kg; ES −0.01, lean mass = 74.6–75.1kg; ES 0.07, fat mass = 13.6–12.9kg; ES −0.17, body fat percentage = 14.8–14.1%; ES −0.19). These data suggest that academy players need time to develop towards profiles congruent with senior players. Moreover, once players reach senior level, body-composition changes are trivial during the pre-season and therefore teams may need to individualise training for players striving to gain muscle mass by reducing other training loads.